(untitled) (Current Problems in Rail Vehicles, 2021)
The first part of this paper describes measurements done on experimental vehicle of Faculty of Transport Engineering – these measurements were used for determination of conversion efficiency of sunshine into electric energy through photovoltaic panels mounted directly on the roof of the vehicle. Next part is focused on statistical processing of data about sunshine from four meteorological stations in Czech Republic. In the last part of this paper are presented simulations results of the drive of the two-source electric motor unit done according to counted efficiency of energy change and statistical data of sunshine. These simulations were done for railway tracks in Czech Republic, real energy impact of photovoltaic panels on the roof of unit was assessed.